2015
DOI: 10.1021/acs.jpclett.5b02460
|View full text |Cite
|
Sign up to set email alerts
|

Air-Stable Surface-Passivated Perovskite Quantum Dots for Ultra-Robust, Single- and Two-Photon-Induced Amplified Spontaneous Emission

Abstract: We demonstrate ultra-air- and photostable CsPbBr3 quantum dots (QDs) by using an inorganic-organic hybrid ion pair as the capping ligand. This passivation approach to perovskite QDs yields high photoluminescence quantum yield with unprecedented operational stability in ambient conditions (60 ± 5% lab humidity) and high pump fluences, thus overcoming one of the greatest challenges impeding the development of perovskite-based applications. Due to the robustness of passivated perovskite QDs, we were able to induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
477
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 486 publications
(498 citation statements)
references
References 52 publications
11
477
4
1
Order By: Relevance
“…High PLQY is one of the main advantages of the colloidal perovskite NCs, prompting researchers to perform intensive investigations for their use as optical gain media for lasing. 13,34,36,37,[106][107][108] Zhu et al 13 have demonstrated wavelengthtunable lasing from single-crystalline organic-inorganic lead perovskite NWs with low thresholds (~220 nJ cm − 2 ) and high quality factors of Q~3600 (Figures 9a-c). The narrowing of the FWHM in the PL spectra by two orders of magnitude above an excitation fluence threshold presented a clear sign of lasing (Figure 9b).…”
Section: Amplified Spontaneous Emission and Lasing With Perovskite Ncsmentioning
confidence: 99%
See 1 more Smart Citation
“…High PLQY is one of the main advantages of the colloidal perovskite NCs, prompting researchers to perform intensive investigations for their use as optical gain media for lasing. 13,34,36,37,[106][107][108] Zhu et al 13 have demonstrated wavelengthtunable lasing from single-crystalline organic-inorganic lead perovskite NWs with low thresholds (~220 nJ cm − 2 ) and high quality factors of Q~3600 (Figures 9a-c). The narrowing of the FWHM in the PL spectra by two orders of magnitude above an excitation fluence threshold presented a clear sign of lasing (Figure 9b).…”
Section: Amplified Spontaneous Emission and Lasing With Perovskite Ncsmentioning
confidence: 99%
“…Perovskite NCs have already shown great promise in many applications such as lasers, LEDs and photovoltaic devices. 10,23,[31][32][33][34][35][36][37][38] Even though the research on perovskite NCs is still in its starting stage, they are expected to have a significant role in the development of modern nanoscience and nanotechnology in the near future. This review provides an overview of the up-to-date developments in the synthesis of hybrid organicinorganic and all-inorganic perovskite NCs, their attractive optical properties and related emerging applications.…”
Section: Introductionmentioning
confidence: 99%
“…For example, to keep a high quantum yield, surface passivation is usually necessary, while long-chain ligands will reduce the conductivity of QDs. In this regard, Pan and coworkers applied a short ligand, di-dodecyl dimethyl ammonium bromide, to passivate CsPbBr 3 QDs and facilitate the carrier transport ability [37]. Consequently, a promoted PL quantum yield of about 71% was achieved, and a higher external quantum efficiency of ~3.0% was obtained.…”
Section: Leds Based On Perovskite Qdsmentioning
confidence: 99%
“…These approaches used hybrid perovskites in the form of powders with vertical cavities [10], cavity-free thin films [11,12], crystals with vertical cavities [13], microdisks/plates with whispering gallery modes (WGMs) [14,15], micro/nanowires with Fabry-Perot (FP) cavities [16,17] and gratings [18], micro/ nanorods with FP cavities [19], cavity-free colloidal quantum dots [20] and WGMs [21], colloidal nanocrystals with WGMs [22], FP cavities [23], and vertical cavities [24]. Compared to ASE, SE typically has a narrower linewidth and obvious threshold, and exhibits beam divergence and polarization [25].…”
mentioning
confidence: 99%
“…All perovskites green-light emitters mentioned above [10,11,[13][14][15][16][17][18][19][20][21][22][23][24] were optically pumped using ultrashort pulses (typically, femtoseconds). An optically pumped NIR perovskite laser using longer pulses (nanoseconds) was recently demonstrated [26], but it was operated in a cryogenic environment.…”
mentioning
confidence: 99%